Calcium iridate as well as preparation method and application thereof

The sol-gel method produces Ca2IrO4, a multi-component iridium-based oxide with a triangular prism structure, addressing the cost and activity limitations of iridium by reducing iridium use and improving catalytic performance in proton exchange membrane water electrolysis.

CN119160957APending Publication Date: 2024-12-20BEIJING SMART ENERGY RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411178597.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The high cost and low abundance of iridium limit its widespread application in proton exchange membrane water electrolysis, while commercial iridium dioxide exhibits low catalytic activity, necessitating the development of new iridium-based catalysts with improved catalytic activity and stability.

Method used

A sol-gel method is used to prepare a multi-component iridium-based oxide, Ca2IrO4, incorporating non-precious metal calcium, which forms a triangular prism structure with controlled crystal growth, enhancing catalytic activity and stability through precise adjustment of the calcium salt feed ratio.

Benefits of technology

The Ca2IrO4 catalyst reduces iridium usage, outperforms IrO2 in oxygen evolution reaction, and demonstrates superior catalytic stability, making it suitable for proton exchange membrane water electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160957A_ABST
    Figure CN119160957A_ABST
Patent Text Reader

Abstract

The invention provides calcium iridate as well as a preparation method and application thereof, and relates to the field of electro-catalytic materials. The preparation method of the calcium iridate comprises the following steps: mixing an iridium source, a calcium salt, an organic acid, an alcohol and water according to a certain proportion, stirring and heating to obtain calcium iridate powder with a triangular prism structure, and then carrying out acid pickling, centrifugal cleaning and collection to obtain the calcium iridate material with the triangular prism structure. The calcium iridate can be used as a catalyst for electrocatalytic water oxidation reaction. By introducing the non-noble metal calcium element and the multi-component iridium-based oxide Ca2IrO4, the dosage of the noble metal iridium element is reduced, the catalytic activity of the oxygen evolution reaction is superior to that of a reference catalyst IrO2, and the catalytic stability is also greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material chemistry and relates to the preparation and application of electrocatalytic materials, and specifically relates to calcium iridate and a preparation method and application thereof. Background Art

[0002] Hydrogen energy, especially green hydrogen, as a clean and efficient energy source, plays an important role in achieving "carbon peak, carbon neutrality" and global energy transformation. Proton exchange membrane water electrolysis technology can work under high pressure and respond to different power inputs within milliseconds, making proton exchange membrane water electrolysis most suitable for coupling with fluctuating energy input. In addition, proton exchange membrane water electrolysis also has the advantages of fast response, high proton conductivity, low ohmic loss and low gas crossover rate. It is most likely to become a hydrogen production method for industrial high-purity and high-efficiency hydrogen production applications. Therefore, this technology has developed most rapidly in the field of electrolytic hydrogen production. So far, iridium-based materials (mainly metallic iridium and iridium-based oxides) are the most suitable electrocatalysts for oxygen evolution reaction in exchange membrane water electrolysis due to their balanced activity and durability. However, due to the low abundance of iridium in the earth's crust and the small annual output, its price is very expensive. How to effectively reduce the amount of precious metal iridium without sacrificing catalytic performance is the key to achieving large-scale application of proton exchange membrane water electrolysis technology. At present, the commonly used method is to use the method of synthesizing multi-element iridium-based oxides to reduce the amount of precious metal iridium by introducing other non-precious metal components. In addition, the commercial rutile structure iridium dioxide has low catalytic activity, and it is urgent to develop new structure iridium-based catalysts to improve catalytic activity. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention provides a calcium iridate and a preparation method and application thereof. By introducing non-precious metal calcium element, the multi-component iridium-based oxide Ca2IrO4 not only reduces the dosage of precious metal iridium element, but also has better catalytic activity in oxygen evolution reaction than the benchmark catalyst IrO2, and the catalytic stability is also greatly improved.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing calcium iridate (Ca2IrO4) comprises the following steps: (1) dissolving an iridium source, a calcium salt and an organic acid in a mixed solvent of alcohol and water to obtain a mixed solution; (2) stirring and dissolving the mixed solution of step (1), drying the sample, and heating the dried sample at high temperature for a certain period of time to obtain a black powder; (3) The black powder obtained in step (2) is soaked in acid, washed with ethanol and water, and dried to obtain the calcium iridate.

[0005] Furthermore, the iridium source is selected from one or more of potassium hexachloroiridate (IV), sodium hexachloroiridate (IV), potassium hexachloroiridate (III), sodium hexachloroiridate (III), iridium chloride, and chloroiridic acid.

[0006] Furthermore, the calcium salt is selected from one or more of calcium carbonate, hydrochloride, sulfate and oxalate.

[0007] Furthermore, the organic acid is selected from one or more of citric acid, acetic acid, tartaric acid, lactic acid, and malonic acid.

[0008] Furthermore, the alcohol is selected from one or more of ethanol, ethylene glycol, propylene glycol, glycerol, and isopropanol.

[0009] Furthermore, the molar ratio of the iridium source to the calcium salt is 1:4-16.

[0010] Furthermore, the molar ratio of the calcium salt to the organic acid is 0.1-4:1.

[0011] Furthermore, the volume ratio of the alcohol to water is 1:0.6-2.

[0012] Furthermore, in step (2), the stirring temperature is 0-50° C., and the stirring time is 0.5-6 h.

[0013] Furthermore, the drying temperature in step (2) is 100-200° C., and the drying time is 4-20 hours.

[0014] Furthermore, the heating time in step (2) is 3 to 10 hours.

[0015] Furthermore, the heating temperature in step (2) is 300-600°C.

[0016] Furthermore, the acid in step (3) is one or more of hydrochloric acid, glacial acetic acid, and perchloric acid, and the concentration of the acid is 0.1-5 mol / L.

[0017] Furthermore, the soaking time in step (3) is 0.5 to 10 hours.

[0018] Furthermore, the number of times of washing in step (3) is 1 to 5 times, and washing is performed until the pH is neutral.

[0019] Furthermore, the sample obtained after washing with ethanol and water in step (3) is centrifuged and then dried.

[0020] The present invention also provides calcium iridate prepared by the above method, wherein the calcium iridate has a triangular prism structure, and its aspect ratio is preferably 1-4.

[0021] Furthermore, the chemical formula of calcium iridate is Ca2IrO4, and its space group belongs to , which is a hexagonal crystal system.

[0022] The present invention also provides the use of calcium iridate prepared by the above method in an electrocatalytic water oxidation reaction.

[0023] The present invention adopts the sol-gel method to prepare the multi-component iridium-based oxide Ca2IrO4, and the organic acid is used as a complexing agent to form a stable complex with metal calcium ions and iridium ions: Ir 3+ / 4+ + R-COOH→Ir(R-COO) x + yH + , Ca 2+ + R-COOH→Ca(R-COO) x + yH + This step ensures that all reactants are evenly distributed and prevents metal ion precipitation; after heating in the oven, the water and alcohol in the solution gradually evaporate, and the metal complex gradually aggregates to form a gel-like substance; after subsequent high-temperature heating, the metal complex forms calcium iridate through solid-phase reaction. In addition, the space group of the polyvalent iridium-based oxide Ca2IrO4 belongs to , belonging to the hexagonal crystal system, different crystal faces mean different surface structures, electronic structures and decalcification abilities, thus affecting the catalytic performance. By adjusting the feed ratio of calcium salt, the growth of specific crystal faces of Ca2IrO4 can be controlled, thereby obtaining Ca2IrO4 with triangular prism structures of different sizes. Different crystal faces will affect the decalcification ability of multi-component iridium-based oxide Ca2IrO4. At the same time, different crystal growth sizes show different catalytic activities in the oxygen evolution reaction under acidic conditions, and show a certain regularity.

[0024] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a sol-gel method to prepare a multi-component iridium-based oxide Ca2IrO4. By introducing a non-precious metal calcium element, the multi-component iridium-based oxide Ca2IrO4 not only reduces the amount of the precious metal iridium element, but also has a catalytic activity for oxygen evolution reaction that is better than that of the benchmark catalyst IrO2, and the catalytic stability is also greatly improved. In addition, the preparation method can control the growth of a specific crystal face of Ca2IrO4 by adjusting the feed ratio of the calcium salt, thereby obtaining Ca2IrO4 with a triangular prism structure of different sizes and different aspect ratios. Different crystal growth sizes and aspect ratios show different catalytic activities and catalytic stability in the oxygen evolution reaction under acidic conditions, so that the catalyst can be effectively regulated according to the requirements for the catalyst in the PEM water electrolysis technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a transmission photograph of the triangular prism structure of calcium iridate prepared in Example 1.

[0026] Figure 2 This is the XRD data of the triangular prism structured calcium iridate prepared in Example 1.

[0027] Figure 3 This is the LSV curve of the oxygen evolution reaction of the triangular prism structure calcium iridate prepared in Example 1 under acidic conditions.

[0028] Figure 4 This is a test diagram of the electrocatalytic stability of the oxygen evolution reaction of the Ca2IrO4-1 sample in Example 1. DETAILED DESCRIPTION

[0029] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.

[0030] Example 1 (1) 0.165 mmol of potassium hexachloroiridate (IV), different amounts of anhydrous calcium chloride (1.33 mmol, 2.66 mmol, 5.22 mmol), and 1.33 mmol of citric acid were weighed and dissolved in a mixed solvent of 5 mL of ethylene glycol and 4 mL of water to obtain a mixed solution.

[0031] (2) The mixed solution obtained in step (1) was stirred at room temperature for 2 h, and then the sample was placed in an oven and dried at 180°C for 12 h; then the dried sample was placed in a muffle furnace and heated at 600°C for 5 h to obtain a black powder.

[0032] (3) The black powder obtained in step (2) was soaked in 1 mol / L hydrochloric acid for 2 h. After being fully protonated, it was washed with ethanol and water for 3 to 5 times until the pH was neutral. The sample was collected by centrifugation and dried to obtain the triangular prism structure calcium iridate materials of the present invention, which were named Ca2IrO4-1, Ca2IrO4-2, and Ca2IrO4-3, respectively.

[0033] In order to observe the morphology of multi-component iridium-based oxide Ca2IrO4 samples, TEM tests were carried out on the above three samples ( Figure 1 ac). It can be observed that the Ca2IrO4 sample has two morphologies, one is a rectangular morphology and the other is a triangular morphology. Therefore, we predict that the sample has a triangular prism morphology. Figure 1It can be seen from the TEM images that as the amount of raw metal calcium ions increases, the Ca2IrO4 sample grows along a specific crystal plane. To confirm this phenomenon, the particle size distribution statistics of 30 different particles in the transmission image of each sample above were performed ( Figure 1 de). The particle sizes of Ca2IrO4-1, Ca2IrO4-2 and Ca2IrO4-3 samples are 32 nm, 35 nm and 48 nm, respectively, and the aspect ratio increases from 1-1.7 to 2-5.5 with the increase of the amount of raw metal calcium ions, realizing the controllability of the aspect ratio of Ca2IrO4 (Table 1).

[0034] The above samples were quantitatively tested by powder XRD. According to the experimental results in the XRD diffraction pattern ( Figure 2 ), it can be found that all the diffraction peaks in the three Ca2IrO4 samples correspond to the corresponding powder diffraction standard cards, proving that all samples are pure phases, and the high strength proves that the above materials are highly crystalline. Figure 2 It can be found that the intensity of the characteristic diffraction peak (111) crystal plane increases with the increase of calcium ion content in the feed amount. This phenomenon shows that the Ca2IrO4 sample grows along a specific crystal plane with the increase of calcium ion content in the feed amount. According to the above results, it can be concluded that increasing the feed amount of raw metal calcium ions in the experiment provides more calcium ions in the solution, increases the supersaturation, and thus promotes the crystal growth process. Specific crystal planes may be more likely to obtain the required Ca source under high concentrations of calcium salts, thereby promoting the preferential growth of Ca2IrO4 in a specific crystal direction. In addition, compared with Ca2IrO4-2 and Ca2IrO4-3, the Ca2IrO4-1 sample has the phenomenon of metal calcium ion desolvation during the catalytic process, and more Ir active sites can be exposed after Ca is dissolved.

[0035] Performance Testing: The catalytic activity of Ca2IrO4-1, Ca2IrO4-2 and Ca2IrO4-3 samples in oxygen evolution reaction was tested under acidic conditions (0.1M HClO4) in a 0.1 M HClO4 three-electrode system. Figure 3 shown.

[0036] exist Figure 3 It can be found that the Ca2IrO4 samples show the following catalytic activity pattern for oxygen evolution reaction: Ca2IrO4-1>Ca2IrO4-2>Ca2IrO4-3. 2When the overpotential of Ca2IrO4-1, Ca2IrO4-2 and Ca2IrO4-3 is 301 mV, 325 mV and 349 mV respectively. In order to explore the electrocatalytic stability of Ca2IrO4 samples in oxygen evolution reaction, the Ca2IrO4 samples were tested by chronopotentiometry at a current density of 10 mA / cm 2 Under the condition of 5 h, the voltage loss of Ca2IrO4-1, Ca2IrO4-2 and Ca2IrO4-3 were 0.7%, 3.2% and 5.1% respectively (Table 1). The electrocatalytic stability test of the oxygen evolution reaction of Ca2IrO4-1 sample is shown in the figure Figure 4 This result shows that after the Ca2IrO4 sample grows along a specific direction, its electrocatalytic activity and stability in oxygen evolution reaction decrease.

[0037] Based on the above results, it can be concluded that among the multi-component iridium-based oxides Ca2IrO4, Ca2IrO4-1 exposes more Ir active sites after Ca dissolution, thus showing the best electrocatalytic activity and stability, achieving a current density of 10 mA / cm at 301 mV. 2 The commercially available iridium oxide catalyst requires an overpotential of 360 mV to reach a current density of 10 mA / cm 2 In addition, in the electrocatalytic stability test, the 5h voltage loss of commercially available iridium oxide was 10.7%, which is much higher than that of the calcium iridate prepared by the present invention. This indicates that the calcium iridate with a triangular prism structure of the present invention can be used as a very excellent anode water oxidation catalyst material for PEM water electrolysis.

[0038] Example 2 (1) Weigh 0.165 mmol of potassium hexachloroiridate (IV), 1.33 mmol of anhydrous calcium chloride, and 0.4 mmol of acetic acid, and dissolve them in a mixed solvent of 5 mL of ethylene glycol and 4 mL of water to obtain a mixed solution.

[0039] (2) The mixed solution obtained in step (1) was stirred at room temperature for 2 h, and then the sample was placed in an oven and dried at 180°C for 12 h; then the dried sample was placed in a muffle furnace and heated at 300°C for 10 h to obtain a black powder.

[0040] (3) The black powder obtained in step (2) is soaked in 1 mol / L hydrochloric acid for 2 h. After being fully protonated, it is washed with ethanol and water for 3 to 5 times until the pH is neutral. The sample is centrifuged and collected. After drying, the triangular prism structure calcium iridate material of the present invention is obtained, which is named Ca2IrO4-4.

[0041] The aspect ratio, electrochemical performance and 5 h voltage loss of Ca2IrO4-4 samples were statistically analyzed (Table 1). It can be seen that the aspect ratio of Ca2IrO4-4 samples is 1.1-1.9, and the voltage loss at 10 mA cm -2 At a current density of , the overpotential is 311 mV and the voltage loss is 2.1% in 5 h.

[0042] Example 3 (1) Weigh 0.165 mmol of iridium chloride, 1.33 mmol of calcium carbonate, and 1.33 mmol of citric acid, and dissolve them in a mixed solvent consisting of 5 mL of ethylene glycol and 4 mL of water to obtain a mixed solution.

[0043] (2) The mixed solution obtained in step (1) was stirred at room temperature for 2 h, and then the sample was placed in an oven and dried at 180°C for 12 h; then the dried sample was placed in a muffle furnace and heated at 500°C for 8 h to obtain a black powder.

[0044] (3) The black powder obtained in step (2) is soaked in 1 mol / L hydrochloric acid for 2 h. After being fully protonated, it is washed with ethanol and water for 3 to 5 times until the pH is neutral. The sample is centrifuged and collected. After drying, the triangular prism structure calcium iridate material of the present invention is obtained, which is named Ca2IrO4-5.

[0045] The aspect ratio, electrochemical performance and 5 h voltage loss of the Ca2IrO4-5 sample were statistically analyzed (Table 1). It can be seen that the aspect ratio of the Ca2IrO4-5 sample is 1.1-2. -2 At a current density of , the overpotential is 316 mV and the voltage loss is 2.6% in 5 h.

[0046] Comparative Example 1 (1) 1.33 mmol of anhydrous calcium chloride, 0.165 mmol of iridium chloride, 10 mL of deionized water, and 5 mL of 0.5 M NaOH were mixed into a 40 mL polytetrafluoroethylene-lined autoclave. The solution was placed in an oven and heated to 260 °C for 3 h; then, the container was cooled naturally at room temperature. The precipitate was filtered and washed twice with deionized water to remove other impurities. Then, it was dried in an oven at 100 °C for 1 h. Finally, the sample was transferred to a crucible and calcined at 700 °C for 3 h.

[0047] (2) The black powder obtained in step (1) was soaked in 1 mol / L hydrochloric acid for 2 h. After being fully protonated, it was washed with ethanol and water for 3 to 5 times until the pH was neutral. The sample was collected by centrifugation and dried to obtain a calcium iridate material named Ca2IrO4-6.

[0048] The Ca2IrO4-6 sample was tested by TEM and the sample was a crystal with irregular morphology.

[0049] The electrochemical performance of Ca2IrO4-6 samples was tested at 10 mA cm -2 At a current density of 2.3 Å, the overpotential was 350 mV and the voltage loss was 21% in 5 h (Table 1).

[0050] Table 1: Based on the above results, it can be concluded that the calcium iridate prepared by the present invention has a triangular prism structure with regular morphology, which has a wider range of application scenarios relative to the irregular morphology of calcium iridate prepared by the prior art. This unique triangular prism morphology not only provides more active sites, but also achieves precise control of the crystal growth direction and size by accurately regulating the feeding ratio of calcium salt, thereby obtaining Ca2IrO4 crystals with different aspect ratios. This structural orderliness and dimensional controllability provide more flexibility for the design of the catalyst, enabling it to better adapt to different catalytic reaction conditions and requirements. In particular, the regular triangular prism morphology observed by TEM test and the high crystallinity confirmed by XRD analysis, and higher catalytic activity and catalytic stability of oxygen evolution reaction, further confirm the superiority of the calcium iridate material of the present invention.

[0051] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing calcium iridate, comprising the steps of: (1) dissolving an iridium source, a calcium salt and an organic acid in a mixed solvent of alcohol and water to obtain a mixed solution; (2) stirring and dissolving the mixed solution of step (1), drying the sample, and heating the dried sample at high temperature for a certain period of time to obtain a black powder; (3) The black powder obtained in step (2) is soaked in acid, washed with ethanol and water, and dried to obtain the calcium iridate.

2. The preparation method according to claim 1, characterized in that: The iridium source is selected from one or more of potassium hexachloroiridate (IV), sodium hexachloroiridate (IV), potassium hexachloroiridate (III), sodium hexachloroiridate (III), iridium chloride, and chloroiridic acid; the calcium salt is selected from one or more of calcium carbonate, hydrochloride, sulfate, and oxalate; the organic acid is selected from one or more of citric acid, acetic acid, tartaric acid, lactic acid, and malonic acid; the alcohol is selected from one or more of ethanol, ethylene glycol, propylene glycol, glycerol, and isopropanol.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the iridium source to the calcium salt is 1:4-16.

4. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the calcium salt to the organic acid is 0.1-4:

1.

5. The preparation method according to claim 1 or 2, characterized in that: The volume ratio of the alcohol to water is 1:0.6-2.

6. The preparation method according to claim 1 or 2, characterized in that: The heating time in step (2) is 3 to 10 hours, and the heating temperature is 300 to 600°C.

7. The preparation method according to claim 1 or 2, characterized in that: The stirring time in step (2) is 0.5-6 hours, and the stirring temperature is 0-50°C.

8. The preparation method according to claim 1 or 2, characterized in that: The drying temperature in step (2) is 100-200° C., and the drying time is 4-20 hours.

9. The preparation method according to claim 1 or 2, characterized in that: The acid in step (3) is one or more of hydrochloric acid, glacial acetic acid, and perchloric acid, and the concentration of the acid is 0.1-5 mol / L.

10. The preparation method according to claim 1 or 2, characterized in that: The soaking time in step (3) is 0.5 to 10 hours.

11. The preparation method according to claim 1 or 2, characterized in that: The number of times of washing in step (3) is 1 to 5 times, and the washing is performed until the pH is neutral.

12. The preparation method according to claim 1 or 2, characterized in that: In step (3), the sample obtained after washing with ethanol and water is centrifuged and then dried.

13. A calcium iridate, characterized in that The method is prepared by any one of claims 1 to 12.

14. The calcium iridate according to claim 13, characterized in that The calcium iridate is a triangular prism structure.

15. The calcium iridate according to claim 13, characterized in that The aspect ratio of the calcium iridate is 1-4.

16. The calcium iridate according to claim 13, characterized in that The chemical formula of calcium iridate is Ca2IrO4, and its space group belongs to , which is a hexagonal crystal system.

17. Use of calcium iridate prepared by the method according to any one of claims 1 to 12 in electrocatalytic water oxidation reaction.